Performance of sustainable SCC mixes with mineral additions for use in precast concrete industry. Issue 3 (3rd May 2016) - García-Taengua, Emili; Sonebi, Mohammed; Crossett, Philip; Taylor, Su; Deegan, Peter; Ferrara, Liberato; Pattarini, Andrea
Abstract : The aim of this research was to study the impact that different mineral powders have on the properties of self-compacting concrete (SCC) in order to obtain relations that make it possible to optimize their dosages for being used in precast concrete applications. Different combinations and contents of cement, mineral additions (active and inert), superplasticizers, and aggregates are considered. A new approach for determining the saturation point of superplasticizers is introduced. The fresh state performance was assessed by means of the following tests: slump flow, V-funnel, and J-ring. Concrete compressive strength values at different ages up to 56 days have been retained as representative of the materials' performance in its hardened state. All these properties have been correlated with SCC proportioning. As a result, a number of recommendations for the precast concrete industry arise to design more stable SCC mixes with a reduced carbon footprint.